2019
DOI: 10.14295/cs.v10i4.3211
|View full text |Cite
|
Sign up to set email alerts
|

Growth and nutrient accumulation in three peach rootstocks until the grafting stage

Abstract: Analysing growth and nutrient accumulation is generally employed for guiding the fertilisation practices in the seedling-production chain. In the production of peach rootstock, such evaluations can provide information to aid can to aid in discrimination available genotypes, especially regarding the efficient use and conversion of fertiliser into dry matter, which can reduce the time required to obtain plants suitable for grafting. The aim of this study, was to investigate the differences in growth and nutrient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…According to Table 1, it was found that substrates 1 and 4 presented a pH value within the range considered appropriate for plant development (5.5 to 6.5) as per the classification described by Menegatti et al (2019). The remaining substrates under test presented pH values lower than those considered satisfactory.…”
Section: Discussionmentioning
confidence: 88%
“…According to Table 1, it was found that substrates 1 and 4 presented a pH value within the range considered appropriate for plant development (5.5 to 6.5) as per the classification described by Menegatti et al (2019). The remaining substrates under test presented pH values lower than those considered satisfactory.…”
Section: Discussionmentioning
confidence: 88%
“…The 'BRS Rubimel'/'Flordaguard' plants generated a very different result, as shown by the values for N accumulation and total accumulated dry matter (Figure 1A), since this combination not only resulted in the highest overall mean value (i.e., 98.3 g kg -1 TDM) for N accumulation between the three rootstocks and across the three periods, but also had the lowest total dry matter per plant (Table 2). According to Menegatti, Souza, and Bianchi (2019b) and Shahkoomahally, Chaparro, Beckman, and Sarkhosh (2020), the genotypes of Prunus rootstocks, in addition to having different nutritional requirements, also accumulate nutrients in different proportions in the various plant organs (i.e., root, stem, and leaves); these are intrinsic characteristics of each genotype, and may compromise recommendations for employing rootstocks that are described as more efficient in the use of any specific nutrient, since usage efficiency does not account for the individual usage of each organ.…”
Section: Resultsmentioning
confidence: 99%
“…In the production of quality seedlings, it is important that the plant has a rapid growth, both in height and in the collet diameter, as the latter variable is decisive for the forest seedlings to be able to field. According to Menegatti et al (2019), it must be between 4.0 and 10 mm, at least. In this sense, the average collet diameter of Agonandra brasiliensis seedlings varied between 4.99 and 2.70 mm, with and without the addition of CRF, respectively, in the different substrates (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%